Coupling and electronic synergistic effects of Fe/CeO2 composite to achieve high efficiency and selectivity for RWGS reaction - Zhenqiong Gou; Chuan Huang; Guilin Zhou; Xiaolei Ren; Lidan Deng; Tao Wang; Qin Peng (Journal of CO2 Utilization, 2024)
Transition metal iron, because of its high oxygen mobility, excellent thermal stability and low price, is often used in the study of RWGS reaction. However, the bottleneck problem of iron-based catalysts is the poor CO2 conversion rate. Herein, the Fe/CeO2 composite catalyst with Fe-O-Ce was successfully constructed, which has both high CO2 conversion and high CO selectivity for the low-temperature RWGS reaction. Furthermore, the influence of Fe0 contents is studied, and the result indicated that the CO2 conversion rate and CO selectivity are up to 50.05% and 100% at 500 ºC by the use of 20Fe/CeO2. Moreover, CeO2 is the best catalyst holder than the others. The physical and chemical properties of the catalysts are investigated by in-situ XPS, XRD, low-temperature N2 absorption-desorption (BET) and CO2-TPD. Nano zero-valent iron (Fe0) is the main active center for the RWGS reaction, which easily releases the outer electrons to activate reactant molecules. The introduction of the CeO2 is conducive to the high dispersion of Fe0 nanoparticles and the formation of abundant active centers. With the increase of Fe loading, the electron-rich Fe0 induces a strong electronic effect on the electron-deficient CeO2. The regularity of catalyst are changed by a large amount of zero-valent iron entering into the CeO2 lattice, then formed a lot of Fe-O-Ce solid solution. A large amount of zero-valent iron enter into the CeO2 lattice, inhibiting the grain growth and aggregation of monometallic species, and promoting nano Fe species highly dispersed on CeO2 carriers, leading more active centers exposure. Meanwhile, the abundant oxygen vacancy on xFe/CeO2 surface is advantage for the adsorption and activation of H2 and CO2 molecules. Therefore, the coupling and electronic synergistic effects of the active component Fe0 and the carrier CeO2 make xFe/CeO2 becoming a promising candidate catalyst for RWGS reaction.